Low Concentrations of Isoflurane Abolish Motor Evoked Responses to Transcranial Electrical Stimulation During Nitrous Oxide/Opioid Anesthesia in Humans - Kalkman, Cor J.; Drummond, John C.; Ribberink, Ari??nne A. (Anesthesia and analgesia, 1991)
To study the feasibility of noninvasive monitoring of motor pathways in anesthetized patients, we evaluated the effect of isoflurane on motor evoked responses to constant-voltage transcranial electrical stimulation (tce-MERs). Reproducible tce-MERs were recordable from the tibialis anterior muscle during nitrous oxide/opioid anesthesia in 11 patients. Before the introduction of isoflurane, tce-MER onset latency was 30.8 +/- 1.9 ms, and amplitude ranged from 19 microV to 2.6 mV (median, 209 microV). Operating conditions necessitated neuromuscular blockade in three patients before administration of isoflurane. In the remaining eight patients, introduction of isoflurane in low concentrations resulted in an immediate increase in the latency and a decrease in the amplitude of tce-MERs. The tce-MERs were completely obliterated in all subjects at end-tidal isoflurane concentrations between 0.2% and 0.6% (median, 0.24%). After discontinuation of isoflurane, the tce-MER returned in all patients. The authors conclude that, during nitrous oxide/opioid anesthesia, with the stimulus and recording variables used, isoflurane even at very low concentrations precludes recording of tce-MERs.